ANALISIS YURIDIS TERHADAP TINDAK PIDANA PENIPUAN YANG DILAKUKAN MELALUI MEDIA ELEKTRONIK (Studi Kasus Putusan Nomor 2378/Pid.Sus/2023/PN.Mdn): Studi Kasus Putusan Nomor 2378/Pid.Sus/2023/PN.Mdn - Lubis, Dahlia Hawani (Universitas Harapan Medan, 2024)
The crime of fraud committed online is specifically regulated in Law Number 19 of 2016 concerning Amendments to Law 11 of 2008 concerning Electronic Information and Transactions which implicitly contains elements that are almost the same as the crime of fraud which is generally regulated in Article 378 of the Criminal Code (KUHP). This study aims to determine the application of criminal law to cases of criminal acts of fraud through electronic media and to determine the judge's consideration in handing down a verdict in Case No. 2378/Pid.Sus/2023/PN.Mdn. This type of research is normative juridical research that uses normative case studies in the form of legal behavior products, for example examining laws. This research was conducted at the Medan City Special Class IA District Court. The results of this study indicate that based on the Decision in case Number 2378/Pid.Sus/2023/PN.Mdn, the author concludes that the defendant was found guilty of committing an ITE crime which is generally a case of fraud. The article charged by the Public Prosecutor, namely Article 45A paragraph (1) Jo Article 28 paragraph (1) of Law No. 19 of 2016 concerning Amendments to Law No. 11 of 2008 concerning ITE, has fulfilled all of its elements based on legal facts both through witness testimony, defendant testimony, and evidence and the application of criminal law in Decision Number 2378/Pid.Sus/2023/PN.Mdn is appropriate and in accordance with regulations.